Non-Apoptotic Role of Apoptotic Caspases in the Drosophila Nervous System - Colon-Plaza, Sarah; Su, Tin Tin (Frontiers in Cell and Developmental Biology, 2022)
An increasing number of studies demonstrate that cells can activate apoptotic caspases but not die and, instead, display profound changes in cellular structure and function. In this minireview, we will discuss observations in the nervous system of Drosophila melanogaster that illustrate non-apoptotic roles of apoptotic caspases. We will preface these examples with similar observations in other experimental systems and end with a discussion of how apoptotic caspase activity might be constrained to provide non-lethal functions without killing the cell.